Identification and estimation of dynamic structural models with unobserved choices - Yingyao Hu; Yi Xin (Centre for Microdata Methods and Practice (cemmap), 2019)
This paper develops identification and estimation methods for dynamic structural models when agents' actions are unobserved by econometricians. We provide conditions under which choice probabilities and latent state transition rules are nonparametrically identified with a continuous state variable in a single-agent dynamic discrete choice model. Our identification results extend to (1) models with serially correlated unobserved heterogeneity and continuous choices, (2) cases in which only discrete state variables are available, and (3) dynamic discrete games. We apply our method to study moral hazard problems in US gubernatorial elections. We find that the probabilities of shirking increase as the governors approach the end of their terms.
Keywords: C10; C14; C18; C51; D72; D82; 330; dynamic discrete choice models; unobserved choice; moral hazard; guber-natorial elections